HEALTH PERCEPTION BY GENDER AND AGE - Gil-Lacruz, Marta (2013)
The main goal of this paper is to elaborate a health diagnose of men and women who live in the same Spanish neighborhood. Although in general Spanish people find themselves healthy, females present more health problems due to cultural differences or due to biological factors. The empirical estimation has been carried out with data drawn from a self-elaborated survey of 1032 people older than 14 years old.